Ochrona tajemnicy zawodowej komornika sądowego - Jabłoński, Mariusz; Węgrzyn, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
In this article the authors:— clarify the concept of the profession of public trust;— clarify the concept of professional secrecy;— underline the special status of a court bailiff court bailiff as a public official;— clarify professional secrecy of court bailiff range of subjective and objective, arisingfrom Article 20 of the Act of 29 August 1997 — on court bailiffs and enforcement procedure.Pursuant to that provision:“Paragraph 1. A bailiff is obliged to keep confidential the circumstances of a case that wereacquired due to performed actions.Paragraph 2. The duty referred a paragraph 1 continues after the cancellation of a bailiff.Paragraph 3. The duty of professional secrecy ceases when a bailiff testifies as a witness or a party before the court or prosecutor, unless the disclosure of professional secrecy jeopardizes the good of the state. In those cases a bailiff may be relieved of the duty of confidentiality by the Minister of Justice.”
Keywords: protection; professional secrecy; bailiff